Updates to the RIFM Criteria Document for fragrance ingredient evaluation - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-propanol, 1,1′,1′,1'-(1,2-ethanediyldinitrilo)tetrakis-, CAS Registry Number 102-60-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, octyl crotonate, CAS Registry Number 22874-79-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, propenylguaethol, CAS Registry Number 94-86-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl 3-hydroxybutyrate, CAS Registry Number 5405-41-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-(p-tert-butylphenyl)-2-methylpropanol, CAS Registry Number 56107-04-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl 3-hydroxyhexanoate, CAS Registry Number 2305-25-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, linoleic acid, CAS Registry Number 60-33-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β-naphthyl isobutyl ether, CAS Registry Number 2173-57-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 1,5-dimethylhexyl acetate, CAS Registry Number 67952-57-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-(4-methyl-3-pentenyl)-3-cyclohexene-1-carbonitrile, CAS Registry Number 68084-04-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexaneethyl acetate, CAS Registry Number 21722-83-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 3,5,5-trimethylcyclohexanol, CAS Registry Number 116-02-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 5-methyl-2-phenyl-2-hexenal, CAS Registry Number 21834-92-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-heptanol, 2,6-dimethyl-,acetate, CAS Registry Number 10250-45-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, phenylacetaldehyde glyceryl acetal, CAS Registry Number 29895-73-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexanemethanol, 2,4-dimethyl-, CAS Registry Number 68480-15-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2,2,6-trimethylcyclohexanone, CAS Registry Number 2408-37-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cis-4-(isopropyl)cyclohexanemethanol, CAS registry number 13828-37-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexanone, 2-ethyl-4,4-dimethyl-, CAS registry number 55739-89-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, squalene, CAS Registry Number 111-02-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β-guaiene, CAS Registry Number 88-84-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 3-hexene, 1,1′,''-[ethylidynestris(oxy)]tris-, (3Z, 3′Z,3"Z)-, CAS registry number 215305-10-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-hydroxyhexanoate, CAS Registry Number 21188-58-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 4-methyl-2-phenyl-2-pentenal, CAS Registry Number 26643-91-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-phenyl-2-butenal, CAS Registry Number 4411-89-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, dodecyldimethylamine oxide, CAS Registry Number 1643-20-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, tricosane, CAS Registry Number 638-67-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 2-nonenoate, CAS registry number 111-79-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-(isopropyl)-β-methylcyclohexanethanol, CAS Registry Number 67634-03-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, undecanol, CAS Registry Number 30207-98-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl cis-5-octenoate, CAS Registry Number 41654-15-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-nonenoate, CAS Registry Number 13481-87-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-methyl-3-penten-2-one, CAS Registry Number 141-79-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-hexenoate, CAS Registry Number 2396-78-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Urinary biomarkers of PAHs, VOCs, OPEs, and metal(loid)s in firefighters responding in the wildland urban interface (WUI) - Miriam M. Calkins; Alexander C. Mayer; Derek J. Urwin; Steve Bertke; Christine Toennis; Shawn C. Beitel; Jeff Hughes; Jamie Gabriel; Antonia M. Calafat; Christopher M. Reese; Julianne Cook Botelho; Maria Ospina; et al. (International Journal of Hygiene and Environmental Health, 2026)

RIFM fragrance ingredient safety assessment, 1-(1,2,3,4,5,6,7,8-octahydro-2,3,8,8-tetramethyl-2-naphthalenyl)ethanone, CAS Registry Number 54464-57-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, docosane, CAS Registry Number 629-97-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl jasmonate, CAS Registry Number 1211-29-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-isobutyl-4-methyltetrahydro-2H-pyran-4-ol, CAS Registry Number 63500-71-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dimyrcene, CAS Registry Number 532-87-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl myristate, CAS Registry Number 124-10-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexane, 1-ethenyl-1-methyl-2,4-bis(1-methylethenyl)-, (1R,2R,4S)-rel-, CAS Registry Number 33880-83-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl myristate, CAS Registry Number 124-06-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-methylpentyl 2-methylvalerate, CAS Registry Number 90397-38-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, pyrazine, methyl (methylthio)-, CAS Registry Number 67952-65-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-propenoic acid, 2-[1-(3,3-dimethylcyclohexyl)ethoxy]-2-methylpropyl ester, CAS Registry Number 820975-49-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, hexadecyl palmitate, CAS Registry Number 540-10-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexane, 1-ethenyl-1-methyl-2-(1-methylethenyl)-4-(1-methylethyl)-, didehydro derivative, CAS Registry Number 68845-33-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, acetyl cedrene, CAS Registry Number 32388-55-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, butyl sulfide, CAS Registry Number 544-40-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, heneicosane, CAS Registry Number 629-94-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl palmitate, CAS Registry Number 628-97-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, sclareol, CAS registry number 515-03-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl octadecanoate, CAS Registry Number 111-61-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexyl methyl pentanone, CAS Registry Number 4927-39-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, heptadecane, CAS Registry Number 629-78-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, hexadecane, CAS Registry Number 544-76-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, oleic acid, CAS Registry Number 112-80-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, pentadecane, CAS Registry Number 629-62-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, tetradecane, CAS Registry Number 629-59-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, nonadecane, CAS Registry Number 629-92-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, octadecane, CAS Registry Number 593-45-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, eicosane, CAS Registry Number 112-95-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessments, ethyl ricinoleate, CAS Registry Number 55066-53-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 4-methyl-8-methylenetricyclo[3.3.1.(3,7)]decan-2-yl acetate, CAS Registry Number 122760-85-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, phytyl acetate, CAS Registry Number 10236-16-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, [2,2-bis[(3,7-dimethyl-2,6-octadienyl)oxy]ethyl]benzene, CAS Registry Number 67634-02-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2,3,5,6-tetramethylpyrazine, CAS Registry Number 1124-11-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cedryl methyl ether, CAS Registry Number 67874-81-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl 2-(formylamino)benzoate, CAS Registry Number 41270-80-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, naphtho[2,1-b]furan, dodecahydro-3a,6,6,9a-tetramethyl-, (3aR,5aS,9aS,9bR)-, CAS Registry Number 6790-58-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, laurel leaf oil, CAS Registry Number 8007-48-5, RIFM ID 476-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, (Z)-2-penten-1-ol, CAS Registry Number 1576-95-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 6-methyl-3,5-heptadien-2-one, CAS Registry Number 1604-28-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isopropylphenylbutanal, CAS Registry Number 125109-85-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl cinnamate, CAS Registry Number 103-26-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, lovage leaf oil, CAS Registry Number 8016-31-7, RIFM ID 813-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β,β,3-trimethyl benzenepropanol, CAS Registry Number 103694-68-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dihydro-β-ionone, CAS registry number 17283-81-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-hexanone, CAS Registry Number 589-38-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl methylphenylglycidate, CAS Registry Number 77-83-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dihydro-α-ionone, CAS Registry Number 31499-72-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, hinoki root oil, CAS Registry Number 91745-97-0, RIFM ID 5487-A2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isobornyl methyl ether, CAS Registry Number 5331-32-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl safranate, CAS registry number 35044-57-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, Bucchu oil, betulina, CAS Registry Number 68650-46-4, RIFM ID 73-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl pyruvate, CAS registry number 617-35-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, thyme oil, red, CAS Registry Number 8007-46-3, RIFM ID 471.E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-methyl-3-tolylpropionaldehyde, CAS Registry Number 41496-43-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, dihydrocarvyl acetate, CAS Registry Number 20777-49-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-2,6-nonadien-1-al, CAS Registry Number 41448-29-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isopulegyl acetate, CAS Registry number 57576-09-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, anisyl alcohol, CAS Registry Number 105-13-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, bicyclo[3.1.0]hexan-3-one, 4-methyl-1-(1-methylethyl)-, CAS Registry Number 1125-12-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 6-isopropyl-2(1H)-octahydronaphthalenone, CAS Registry Number 34131-98-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl 3-phenylglycidate, CAS Registry Number 121-39-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, citral, CAS Registry Number 5392-40-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 1,6-octadien-3-ol, 3,7-dimethyl-, acid-isomerized, CAS Registry Number 73018-51-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 1,1-dimethoxycyclododecane, CAS Registry Number 950-33-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-ethyl-5-methoxybicyclo[2.2.1]heptane, CAS registry number 122795-41-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, styrax absolute, CAS registry Number 8024-01-9, RIFM ID 6877.K2.1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, α,α-dimethyl-p-ethylphenylpropanal, CAS Registry Number 67634-15-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, α-hexylcinnamaldehyde, CAS Registry Number 101-86-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-octalactone, CAS Registry number 104-50-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-methoxybenzoic acid, CAS Registry Number 100-09-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-methyl-2-butenyl acetate, CAS Registry Number 1191-16-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-hexalactone, CAS Registry Number 695-06-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, myristic acid, CAS Registry Number 544-63-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isobutyric acid, CAS Registry Number 79-31-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-decalactone, CAS Registry Number 706-14-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-undecalactone, CAS Registry Number 104-67-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isovaleric acid, CAS Registry Number 503-74-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-nonalactone, CAS Registry Number 104-61-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

2nd update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-1,6-nonadien-3-ol, CAS Registry Number 10339-55-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

2nd update to RIFM fragrance ingredient safety assessment, linalool, CAS Registry number 78-70-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2H-indeno[4,5b] furan, decahydro-2,2,6,6,7,8,8-heptamethyl, CAS Registry Number 476332-65-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-dodecalactone, CAS Registry Number 2305-05-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, palmitic acid, CAS Registry number 57-10-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2,6,8-trimethylnonan-4-one, CAS Registry Number 123-18-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyric acid, CAS Registry number 116-53-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,8-dimethyl-4,9-decadienal, CAS Registry number 71077-31-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cedrene, CAS Registry Number 11028-42-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 5-methyl-3-heptanone, CAS Registry Number 541-85-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, iris pallida oil, CAS registry number 8002-73-1, RIFM ID 265.A2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 8H-indeno(4,5-B)furan,2,3,3a,4,5,5a,6,7,8a,9-decahydro-2,6,6,7,8,8-hexamethyl mixture of isomers, CAS Registry Number 338735-71-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-nonanone, CAS Registry Number 821-55-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-undecanone, CAS Registry Number 112-12-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-octanone, CAS registry number 106-68-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-decanone, CAS Registry Number 693-54-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-heptanone, CAS Registry Number 110-43-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-heptalactone, CAS Registry Number CAS # 105-21-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-valerolactone, CAS Registry Number 108-29-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, lauric acid, CAS Registry Number 143-07-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-octanone, CAS Registry Number 111-13-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, benzoin infusion, Sumatra, CAS Registry Number 9000-05-9, RIFM ID 104-K2.31 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4-heptanone, CAS Registry Number 123-19-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-heptanone, CAS Registry Number 106-35-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, myrtenol, CAS Registry Number 515-00-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenylpropionic acid, CAS registry number 501-52-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hexyl phenylacetate, CAS Registry Number 5421-17-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl cyclohexadiene (mixture of isomers), CAS Registry Number 30640-46-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, decanoic acid, CAS Registry Number 334-48-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 5-methyl-5-propyl-2-(1-methylbutyl)-1,3-dioxan, CAS Registry Number 80480-24-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, octanoic acid, CAS Registry Number 124-07-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Corrigendum to “RIFM fragrance ingredient safety assessment, 1,3,5-undecatriene, CAS Registry Number 16356-11-9” [Food Chem. Toxicol. (2024 Mar) 183 Suppl 1 114303. doi: 10.1016/j.fct.2023.114303. Epub 2023 Dec 4] - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-isopropylacetophenone, CAS Registry Number 645-13-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, nonanoic acid, CAS Registry Number 112-05-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4H-4a,9-methanoazuleno[5,6-d]-1,3-dioxole, octahydro-2,2,5,8,8,9a-hexamethyl-, (4aR,5R,7aS,9R)-, CAS Registry Number 211299-54-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, spiro[5.5]undec-8-en-1-one, 2,2,7,9-tetramethyl-, CAS Registry Number 502847-01-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-tolyl 3-methylcrotonate, CAS Registry Number 24700-20-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hexanoic acid, CAS Registry Number 142-62-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-1,3-dioxolane, CAS Registry Number 33941-99-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-hydroxyacetophenone, CAS Registry Number CAS # 118-93-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4-isopropyl-2-methoxy-1-methylbenzene, CAS Registry Number 6379-73-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1-ethynylcyclohexyl acetate, CAS Registry Number 5240-32-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,4a,5,9b-tetrahydroindeno[1,2-d]-1,3-dioxine, CAS Registry Number 18096-62-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenyl-1-propanol, CAS Registry Number 122-97-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzaldehyde, CAS Registry Number 100-52-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, benzeneacetonitrile, a-butylidene-, (Z), CAS Registry Number 130786-09-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, geraniol, CAS registry number 106-24-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-phenoxyethanol, CAS Registry number 122-99-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, cinnamyl alcohol, CAS Registry Number 104-54-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl alcohol, CAS Registry Number 100-51-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, benzoic acid, 2-[[3-(4-methoxyphenyl)-2-methylpropylidene]amino]-, methyl ester, CAS registry number 111753-62-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

2nd update to RIFM fragrance ingredient safety assessment, 4-carvomenthenol, CAS Registry Number 562-74-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-tert-butylcyclohexyl acetate, CAS registry number 88-41-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-tert-butylcyclohexyl acetate, CAS Registry Number 31846-06-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-tert-butylcyclohexyl acetate, CAS Registry Number 32210-23-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

P30-67 Enhancing Photoallergy Risk Assessment of Fragrance Chemicals through Adopting the ROS Assay into a Tiered Testing Strategy - C. Deodhar; G. Ritacco; D. Botelho (Toxicology Letters, 2025)

Molecular modelling of diterpene compounds from copaifera oleoresin as potential bioactive compounds against SARS‑CoV‑2: calculations of density functional theory and in silico ADME-Tox properties - Rayssa Ribeiro; Fernanda D. Botelho; Samir F. A. Cavalcante; Marcelo C. dos Santos; Valdir F. Veiga-Junior (Natural Product Research, 2025)

Developing productivity and susceptibility attributes towards a rapid management-risk assessment of seaweed - D. Milla-Figueras; P. Torres; A.Z. Botelho; A. Larrea; M.I. Parente; P. Afonso (Algal Research, 2025)

RIFM fragrance ingredient safety assessment, phenyl salicylate, CAS Registry Number 118-55-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, fenchone, CAS Registry Number 1195-79-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, phenethyl acetate, CAS registry number 103-45-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hydroxycitronellal diethyl acetal, CAS Registry Number 7779-94-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amylcyclohexyl acetate (mixed isomers), CAS Registry Number 67874-72-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, octanal dimethyl acetal, CAS Registry Number 10022-28-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, linalyl hexanoate, CAS Registry Number 7779-23-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylundecanal dimethyl acetal, CAS Registry Number 68141-17-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hydroxycitronellal dimethyl acetal, CAS Registry number 141-92-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-isobutylquinoline, CAS registry number 93-19-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-methyl quinoline, CAS registry number 91-63-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyisooctane, CAS Registry Number 69178-43-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, nonane, 1,1-diethoxy-, CAS Registry Number 54815-13-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1,1-diethoxy-3,5,5-trimethylhexane, CAS registry number 86198-35-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-(methylpropyl)quinoline, CAS registry number 1333-58-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, decanal dimethyl acetal, CAS Registry Number 7779-41-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-isopropylphenol, CAS Registry Number 99-89-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-buten-2-one, 4-(2,2,3-trimethyl-6-methylenecyclohexyl)-, CAS registry number 79-68-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, heptanal dimethyl acetal, CAS registry number 10032-05-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyhexane, CAS registry number 3658-93-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-acetyl-5-methylfuran, CAS Registry Number 1193-79-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isophytol, CAS Registry Number 505-32-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-furyl methyl ketone, CAS Registry Number 1192-62-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, savory winter oil, CAS Registry Number 90106-57-3, RIFM ID 1181-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, ho wood oil, CAS Registry Number 8022-91-1, RIFM ID 217-D2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, dimethylcyclohex-3-ene-1-carbaldehyde (isomer unspecified), CAS Registry Number 27939-60-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 6-methyl-2-(4-methyl-3-cyclohexen-1-yl)-5-hepten-2-ol, CAS Registry Number 515-69-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, maltol, CAS registry number 118-71-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-(5,5,6-trimethylbicyclo[2.2.1]hept-2-yl)cyclohexan-1-ol, CAS registry number 3407-42-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl valerate, CAS Registry Number 10361-39-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isocyclocitral, CAS Registry Number 1335-66-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, ho leaf oil, CAS Registry Number 8022-91-1, RIFM ID 217-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, ho bark oil, CAS registry number 8022-91-1, RIFM ID 217-C2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl formate, CAS Registry Number 104-57-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyheptane, CAS Registry Number 688-82-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-octanol, CAS registry number 111-87-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,4a,6,7,8,8a-hexahydro-1,4-methanonaphthalen-5(1H)-one, CAS Registry Number 51519-65-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amyl hexanoate, CAS registry number 540-07-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, undecanal, CAS Registry Number 112-44-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, N-benzoylanthranilic acid, CAS Registry Number 579-93-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, undecyl alcohol, CAS Registry Number 112-42-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-tridecanol, CAS Registry Number 112-70-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, lauryl alcohol, CAS Registry Number 112-53-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, hexyl alcohol, CAS Registry Number 111-27-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, ethyl maltol, CAS Registry Number 4940-11-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, butyrophenone, CAS Registry Number 495-40-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, p-tolyl phenylacetate, CAS Registry Number 101-94-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl decanoate, CAS Registry Number 110-42-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-decanol, CAS registry number 112-30-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, clove bud absolute, CAS Registry Number 8000-34-8, RIFM ID 583-F2.1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, nonyl alcohol, CAS Registry Number 143-08-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methoxy dicyclopentadiene carboxaldehyde, CAS Registry Number 86803-90-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, octahydro-4,7-methano-1H-indenecarbaldehyde, CAS Registry Number 30772-79-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, acetophenone, CAS Registry number 98-86-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, Sage oil, Spanish, CAS Registry Number 8022-56-8, RIFM ID 479-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

2nd Update to RIFM fragrance ingredient safety assessment, α-amylcinnamaldehyde, CAS Registry Number 122-40-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Corrigendum to “RIFM fragrance ingredient safety assessment, vanillin isobutyrate, CAS Registry Number 20665-85-4” [Food Chem. Toxicol. 197 Supplement 1 (2024) 115141 ISSN 0278–6915] - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, heptyl alcohol, CAS registry number 111-70-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-acetoxy-2,5-dimethyl-3(2H)furanone, CAS Registry Number 4166-20-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl propionate, CAS Registry Number 105-68-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl propionate, CAS Registry Number 540-42-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-(p-methoxyphenyl)-2-butanone, CAS Registry Number 104-20-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cis-6-nonenal, CAS registry number 2277-19-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenylbutanal, CAS registry number 16251-77-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, cyclohexanepropanol, α-ethyl-2,2,6-trimethyl-, CAS Registry Number 60241-52-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl 3,7-dimethyl-6-octenoate, CAS registry number 2270-60-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, (1aα,4α,7aα)-1a,3,3,4,6,6-hexamethyl-1a,2,3,4,5,6,7,7a-octahydronapth[3,3-b]oxirene, CAS Registry Number 94400-98-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cyclododecyl formate, CAS Registry Number 59052-82-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, (Z)-4-dodecenal, CAS registry number 21944-98-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-phenylpropionaldehyde, CAS registry number 93-53-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4,5-dihydro-3(2H)thiophenone, CAS Registry Number 1003-04-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 9-undecenal, CAS Registry Number 143-14-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, β-methyl-benzenepentanal, CAS registry number 55066-49-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, nonanal, CAS registry number 124-19-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, trans-4-decen-1-al, CAS Registry Number 65405-70-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl formate, CAS Registry Number 110-45-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 8-undecenal, CAS registry number 58296-81-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, linalyl isovalerate, CAS Registry Number 1118-27-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, hexanal, CAS Registry Number 66-25-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,8-dimethyl-7-nonen-2-ol, CAS Registry Number 40596-76-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-ethoxy-4-(methoxymethyl)phenol, CAS Registry Number 5595-79-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, β-caryophyllene alcohol, CAS registry number 472-97-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, acetylcarene, CAS Registry Number 3608-11-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-heptenal, CAS Registry Number 6728-31-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl alcohol, CAS Registry Number 123-51-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-phenoxyethyl isobutyrate, CAS registry number 103-60-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, linalyl isobutyrate, CAS Registry Number 78-35-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-tetradecanol, CAS Registry Number 112-72-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-hexenoic acid, CAS Registry Number 4219-24-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl 2-nonynoate, CAS Registry Number 111-80-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-(4-methyl-3-cyclohexenyl)butanol, CAS Registry Number 15760-18-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, dihydro-β-ionol, CAS Registry Number 3293-47-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, p-tolylacetaldehyde, CAS Registry Number 104-09-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, β-pinene, CAS Registry Number 127-91-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, geranyl crotonate, CAS Registry Number 56172-46-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-4(2,2,3-trimethyl-3-cyclopentenyl)butanol, CAS Registry Number 72089-08-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-methylbutyl valerate, CAS Registry Number 2050-09-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, octanal, CAS Registry Number 124-13-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, tricyclo[3.3.1.1.(3.7)]decan-2-ol, 4-methyl-8-methylene-, CAS Registry Number 122760-84-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, heptanal, CAS registry number 111-71-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyl butyrate, CAS Registry Number 51115-64-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amyl alcohol, CAS Registry Number 71-41-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, pentanoic acid, 2-methylbutyl ester, CAS Registry Number 55590-83-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3,4-xylenol, CAS Registry Number 95-65-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyl acetate, CAS Registry Number 624-41-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl butyrate, CAS Registry Number 539-90-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, decanal, CAS registry number 112-31-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cedryl formate, CAS Registry Number 39900-38-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-(4-methoxyphenyl)-3-methylbutan-2-one, CAS Registry Number 67828-19-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-(p-methoxyphenyl)-2-propanone, CAS Registry Number 122-84-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, trans-2-hexenyl acetate, CAS Registry Number 2497-18-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, isolongifolene oxide, CAS Registry Number 26619-69-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-menth-8-en-2-one, CAS Registry Number 7764-50-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, l-menthyl (R,S)-3-hydroxybutyrate, CAS Registry Number 108766-16-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, butyl alcohol, CAS registry number 71-36-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, tridecanal, CAS registry number 10486-19-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cedr-8-ene epoxide, CAS Registry Number 13567-39-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, geranyl tiglate, CAS Registry Number 7785-33-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4′-tert-butyl-2′,6′-dimethylacetophenone, CAS Registry Number 2040-10-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, ethyl trans-2,cis-4-decadienoate, CAS registry number 3025-30-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl acetate, CAS Registry Number 123-92-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-hexadecanol, CAS Registry Number 36653-82-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl acetate, CAS Registry Number 110-19-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cis-3-hexenyl salicylate, CAS Registry Number 65405-77-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-2-hepten-6-ol, CAS registry number 1569-60-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, nopyl acetate, CAS registry number 128-51-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl butyrate, CAS Registry Number 106-27-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, piperonal, CAS Registry Number 120-57-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzothiazole, CAS Registry Number 95-16-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-cyclopropylmethyl-4-methoxybenzene, CAS registry number 16510-27-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3,7-dimethyl-2-methylenocta-6-enal, CAS registry number 22418-66-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl alcohol, CAS Registry Number 78-83-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylpropyl pentanoate, CAS Registry Number 10588-10-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-(3-heptyl)-1,3-dioxolane, CAS Registry Number 4359-47-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, ethyl 2-methyl-3-pentenoate, CAS Registry Number 1617-23-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, vanillin isobutyrate, CAS Registry Number 20665-85-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-methylbutanal diethyl acetal, CAS Registry Number 3842-03-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, (4-methylphenoxy)acetaldehyde, CAS Registry Number 67845-46-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, propyl alcohol, CAS Registry Number 71-23-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, dibenzyl ether, CAS Registry number 103-50-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, β-ionyl acetate, CAS Registry Number 22030-19-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cinnamyl cinnamate, CAS Registry Number 122-69-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,6-xylenol, CAS Registry Number 576-26-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isobutyl formate, CAS registry number 542-55-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl 2-octynoate, CAS Registry Number 111-12-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexanone 1,3-butylene glycol ketal, CAS Registry Number 6413-26-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, zingerone, CAS Registry Number 122-48-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-ethoxy-4-[(1-methylethoxy)methyl] phenol, CAS Registry number 96840-56-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, diethyl malonate, CAS registry number 105-53-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-(4,8-dimethylnona-3,7-dienyl)pyridine, CAS Registry Number 38462-23-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-propanediol, 2,2-dimethyl-, 1,3-diacetate, CAS registry number 13431-57-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-(cis-3-hexenyloxy)propanenitrile, CAS Registry Number 142653-61-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isobutyl benzoate, CAS registry number 120-50-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-(4-methyl-3-penten-1-yl)-2(5H)-furanone, CAS Registry number 61315-75-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-butyl-4,4,6-trimethyl-1,3-dioxane, CAS registry number 54546-26-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-(2-tert-butyl cyclohexyloxy)-2-butanol, CAS Registry Number 139504-68-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 2-methylbutyrate, CAS Registry Number 7452-79-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzyl salicylate, CAS registry number 118-58-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl benzoate, CAS registry number 6789-88-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl isovalerate, CAS Registry Number 556-24-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, cyclohexanecarboxylic acid, CAS Registry Number 98-89-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl isobutyrate, CAS registry number 97-62-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 6,8-dimethylnonan-2-ol, CAS registry number 70214-77-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isoamyl benzoate, CAS registry number 94-46-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl isobutyrate, CAS registry number 547-63-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 10-undecenoic acid, heptyl ester, CAS registry number 68141-27-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-(4-methylcyclohex-3-enyl)-3-butenyl acetate, CAS registry number 6819-19-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, p-methyl-α-amyl cinnamic aldehyde, CAS Registry Number 84697-09-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl salicylate, CAS registry number 119-36-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl 2-methylbutyrate, CAS Registry Number 868-57-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, amyl salicylate, CAS Registry Number 2050-08-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-methyl-2-(1-methylpropyl)cyclohexyl acetate, CAS Registry number 72183-75-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cis-3-hexenyl benzoate, CAS Registry Number 25152-85-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isoamyl salicylate, CAS Registry Number 87-20-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-oxaspiro[4.5]decan-2-one, 8-(1-methylethyl)-, trans-, CAS Registry Number 4625-90-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-methyl-2-pentanol, CAS registry number 108-11-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,6-dimethyl-4-heptanol, CAS registry number 108-82-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, heptyl acetate, CAS registry number 112-06-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-5-phenylpentanol, CAS Registry Number 25634-93-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl formate, CAS registry number 629-33-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl butyrate, CAS Registry Number 2639-63-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, furfural, CAS Registry Number 98-01-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, octyl acetate, CAS Registry Number 112-14-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, octyl formate, CAS registry number 112-32-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-oxaspiro[4.5]decan-2-one, 8-ethyl-, trans-, CAS Registry Number 91069-40-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, p-mentha-1,8-dien-7-ol, CAS Registry Number 536-59-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 7-isopropyl-1,4-dimethylazulene, CAS registry number 489-84-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-isopropyl-1-methylcyclohexene, CAS registry number 29350-67-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl α-ionone, CAS Registry Number 79-78-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, lauryl acetate, CAS Registry Number 112-66-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-oxaspiro[4.5]decan-2-one, 8-methyl-, CAS Registry number 94201-19-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-methyl-5-phenylpentanol, CAS Registry Number 55066-48-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, nonyl acetate, CAS registry number 143-13-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, octyl butyrate, CAS Registry Number 110-39-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-(methylthio)hexyl acetate, CAS registry number 51755-85-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,2-dimethyl-3-phenylpropanol, CAS registry number 13351-61-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-(cis-3-hexenyl)dihydro-5-methyl-2(3H)furanone, CAS Registry Number 70851-61-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, o-phenyl anisole, CAS registry number 86-26-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, geranyl acetate, CAS registry number 105-87-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, geranyl linalool, CAS registry number 1113-21-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ionone (mixed isomers), CAS registry number 8013-90-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl salicylate, CAS Registry Number 118-61-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-phenyl-3-buten-2-ol, CAS registry number 17488-65-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isopropyl acetate, CAS registry number 108-21-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl propionate, CAS Registry Number 2445-76-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, α-butylcinnamaldehyde, CAS registry number 7492-44-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, decyl acetate, CAS Registry Number 112-17-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, musk ketone, CAS registry number 81-14-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, veratraldehyde, CAS Registry Number 120-14-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isopropyl butyrate, CAS Registry Number 638-11-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-hydroxybenzoic acid, CAS Registry Number 69-72-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-methylfurfural, CAS registry number 620-02-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl acetate, CAS registry number 142-92-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-4-phenylpentanol, CAS registry number 92585-24-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-4-phenylbutyraldehyde, CAS Registry Number 40654-82-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cis-3-hexenal, CAS Registry Number 6789-80-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, pinus nigra oil, CAS Registry Number 8000-26-8, RIFM ID 1068-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexyl phenylacetate, CAS Registry Number 42288-75-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,4,5,6,6-pentamethylheptan-2-ol, CAS registry number 87118-95-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-cyclohexadiene-1-carboxylic acid, 4,6,6-trimethyl-, ethyl ester, CAS Registry Number 100520-15-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2(4H)-benzofuranone, 5,6-dihydro-3,6-dimethyl-, CAS Registry Number 80417-97-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, β-methylphenethyl alcohol, CAS Registry Number 1123-85-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, N-ethyl-N-(3-methylphenyl)propionamide, CAS Registry Number 179911-08-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl cinnamate, CAS Registry number 1866-31-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-hexene, 1-[(2-methyl-2-propenyl)oxy]- (3Z)-, CAS Registry Number 292605-05-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, lavandin abrialis, CAS registry number 8022-15-9, RIFM ID 1048554 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, rotundone, CAS Registry Number 18374-76-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methylheptenol, CAS Registry Number 1335-09-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,4-bis(ethoxymethyl)cyclohexane, CAS Registry Number 54889-63-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, bicyclo[2.2.1]heptan-2-ol, 1,3,3-trimethyl-, benzoate, CAS Registry Number 55066-54-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methylbutyl hexanoate, CAS registry Number 2601-13-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, propanoic acid, 2-methyl-, cyclohexyl ester, CAS Registry Number 1129-47-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,7-dimethyl-1,6-nonadien-3-yl acetate, CAS Registry Number 61931-80-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-heptanol, 3,6-dimethyl-, CAS registry number 1247790-47-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl cyclohexanecarboxylate, CAS Registry Number 3289-28-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalyl butyrate, CAS Registry Number 78-36-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 6-butyl-2,4-dimethyldihydropyrane, CAS Registry Number 24237-00-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,7-dimethyl-7-methoxyoctan-2-ol, CAS registry number 41890-92-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-isopropyl-N,2,3-trimethylbutyramide, CAS registry number 51115-67-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, piperonyl acetate, CAS registry number 326-61-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, α-propylphenethyl alcohol, CAS registry number 705-73-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl heptanoate, CAS registry number 142-19-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-(4-methylphenoxy)ethanol, CAS Registry Number 15149-10-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, nonanoyl 4-hydroxy-3-methoxybenzylamide, CAS Registry Number 2444-46-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl hexanoate, CAS Registry Number 123-68-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phenethyl alcohol, CAS Registry Number 60-12-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, benzenepropanol, a,ß-dimethyl-, CAS Registry Number 56836-93-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-(2-oxopropyl)-2-pentylcyclopentanone, CAS Registry Number 40942-73-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1,3,3-trimethyl-2-norbornanyl acetate, CAS registry number 13851-11-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, tetrahydrogeranial, CAS Registry Number 5988-91-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isobornyl acetate, CAS Registry Number 125-12-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, nerolidyl acetate (isomer unspecified), CAS registry number 2306-78-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, oxacyclohexadecane-2,13-dione, CAS registry number 38223-29-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, (Z)-octadec-9-enol, CAS registry number 143-28-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, linalyl acetate, CAS registry number 115-95-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-naphthalenol, 1,2,3,4,4a,5,8,8a-octahydro-2,2,6,8-tetramethyl-, CAS Registry Number 103614-86-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-inden-5-yl pivalate, CAS Registry Number 68039-45-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-inden-5-yl isobutyrate, CAS Registry Number 67634-20-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, tricyclodecanyl acetate, CAS registry number 64001-15-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isobornyl propionate, CAS Registry Number 2756-56-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl octanoate, CAS Registry Number 4230-97-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalyl formate, CAS registry number 115-99-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, nerol oxide, CAS Registry Number 1786-08-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, l-menthyl D-lactate, CAS registry number 59259-38-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalyl propionate, CAS registry number 144-39-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, trichloromethyl phenyl carbinyl acetate, CAS Registry number 90-17-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-hexen-1-ol, 5-methyl-2-(1-methylethenyl)-, CAS registry number 58461-27-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, dihydro-α-terpineol, CAS Registry Number 498-81-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-hexylcyclopentanone, CAS registry number 13074-65-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-2-butyl isobutyrate, CAS registry number 10031-71-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, d,l-menthone 1,2-glycerol ketal, CAS Registry Number 63187-91-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-cyclohexyl-2-methyl-2-butanol, CAS registry number 83926-73-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4′-hydroxy-3′-methoxyacetophenone, CAS Registry Number 498-02-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2,2,4-trimethyl-4-phenyl-butane-nitrile, CAS Registry Number 75490-39-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, thymol, CAS Registry Number 89-83-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl cinnamate, CAS Registry Number 103-36-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-methyl-2-butenyl benzoate, CAS Registry Number 5205-11-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methylcyclooctyl carbonate, CAS Registry Number 61699-38-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-p-tolylethanol, CAS registry number 699-02-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-1,3,6-octatriene, CAS Registry Number 13877-91-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,1-dimethyl-2-phenylethyl isobutyrate, CAS Registry Number 59354-71-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, amyl cinnamate, CAS Registry Number 3487-99-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-2-butanol, CAS Registry Number 103-05-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, benzenepropanenitrile, 4-ethyl-α,α.-dimethyl-, CAS Registry Number 134123-93-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl 2,4-dihydroxy-m-toluate, CAS Registry Number 33662-58-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2H-1,5-benzodioxepin-3(4H)-one, 7-(1-methylethyl)-, CAS Registry Number 950919-28-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 2-ethylhexanoate, CAS Registry Number 2983-37-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexyl salicylate, CAS registry number 25485-88-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment,α-methylbenzyl alcohol, CAS registry number 98-85-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-isopropylcyclohexanol, CAS Registry Number 4621-04-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, acetaldehyde, diphenethyl acetal, CAS Registry Number 122-71-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, α,α-dimethylphenethyl alcohol, CAS Registry Number 100-86-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, citronellyl ethyl oxalate, CAS Registry Number 60788-25-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 2-tert-butylcyclohexyl carbonate, CAS Registry Number 67801-64-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 2,3,6-trimethylcyclohexyl carbonate, CAS Registry Number 93981-50-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-octyl acetate, CAS registry number 4864-61-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, exo-2-[(1,7,7-trimethylbicyclo[2.2.1]hept-2-yl)oxy]ethanol, CAS Registry Number 7070-15-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-propanol, reaction products with boron trifluoride and 5-ethylidenebicyclo[2.2.1]hept-2-ene, CAS registry number 90530-04-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1-propanol, 2-methyl-3-[(1,7,7-trimethylbicyclo-[2.2.1]hept-2-yl)oxy]-, CAS Registry Number 128119-70-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-nonanediol acetate (mixed esters), CAS Registry Number 1322-17-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3,12-tridecadienenitrile, CAS Registry Number 134769-33-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexanoic acid, 4-methyl-, CAS registry number 1561-11-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-ethyloctanoic acid, CAS registry number 16493-80-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methylhexanoic acid, CAS registry number 4536-23-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methylheptanoic acid, CAS registry number 1188-02-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, butyl 2-methylvalerate, CAS Registry Number 6297-41-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, N,N-diethyloctamide, CAS registry number 996-97-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phenethyl salicylate, CAS Registry Number 87-22-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzonitrile, 3,4-dimethyl-, CAS Registry Number 22884-95-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-allyl-2-methoxyphenyl benzyl ether, CAS Registry Number 57371-42-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3,6-nonadien-1-ol, CAS Registry Number 76649-25-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 2-methylpentanoate, CAS Registry Number 39255-32-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, linalyl cinnamate, CAS registry number 78-37-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 3,5,5-trimethylhexanoate, CAS Registry Number 67707-75-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-methyloctanoic acid, CAS Registry Number 54947-74-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, butyl 10-undecenoate, CAS Registry Number 109-42-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methylvaleric acid, CAS Registry Number 97-61-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-methylpentanoic acid, CAS registry number 105-43-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-methylnonanoic acid, CAS Registry Number 45019-28-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-ethylbutyric acid, CAS Registry Number 88-09-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cis- and trans-p-1(7),8-menthadien-2-yl acetate, CAS registry number 71660-03-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, diethyldimethylcyclohex-2-en-1-one, CAS Registry Number 68845-36-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-phenyl-3-buten-1-yl acetate, CAS Registry Number 7306-12-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, spiro[1,3-dioxolane-2,8′(5′H)-[2H-2,4a]methanonaphthalene],hexahydro-1′,1′,5′,5′-tetramethyl-, [2′S-(2′α,4′aα,8′aα)]-, CAS Registry Number 154171-77-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, p-tolyl alcohol, CAS Registry Number 589-18-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-methylpentanoic acid, CAS Registry Number 646-07-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, dihydromyrcenol, CAS registry number 18479-58-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-ethyl-2,3,4,5-tetramethylcyclohexen-1-one, CAS Registry Number 17369-60-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexanol, 2-methoxy-4-propyl-, CAS Registry Number 23950-98-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 10-undecenoate, CAS Registry Number 692-86-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, p-tert-butyldihydrocinnamaldehyde, CAS Registry Number 18127-01-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isoeugenyl phenylacetate, CAS registry number 120-24-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, menthyl acetate (isomer unspecified), CAS registry number 16409-45-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, Mandarin oil terpenes, CAS registry number 68953-04-8, RIFM ID 250-G2.30 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, orange essence oil, CAS Registry Number 68514-75-0, RIFM ID 192-G2.10 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Per- and polyfluoroalkyl substances (PFAS), perceived stress, and depressive symptoms in a prospective cohort study of black women - Samantha Schildroth; Birgit Claus Henn; Anissa I. Vines; Ruth J. Geller; Sharonda M. Lovett; Chad M. Coleman; Traci N. Bethea; Julianne Cook Botelho; Antonia M. Calafat; Chad Milando; Donna D. Baird; Ganesa Wegienka; et al. (Science of The Total Environment, 2024)

Cost–benefit analysis of ecosystem modeling to support fisheries management - Matthew H. Holden; Eva E. Plagányi; Elizabeth A. Fulton; Alexander B. Campbell; Rachel Janes; Robyn A. Lovett; Montana Wickens; Matthew P. Adams; Larissa Lubiana Botelho; Catherine M. Dichmont; Philip Erm; Kate J. Helmstedt; et al. (Journal of Fish Biology, 2024)
Mathematical and statistical models underlie many of the world's most important fisheries management decisions. Since the 19th century, difficulty calibrating and fitting such models has been used to justify the selection of simple, stationary, single‐species models to aid tactical fisheries management decisions. Whereas these justifications are reasonable, it is imperative that we quantify the value of different levels of model complexity for supporting fisheries management, especially given a changing climate, where old methodologies may no longer perform as well as in the past. Here we argue that cost‐benefit analysis is an ideal lens to assess the value of model complexity in fisheries management. While some studies have reported the benefits of model complexity in fisheries, modeling costs are rarely considered. In the absence of cost data in the literature, we report, as a starting point, relative costs of single‐species stock assessment and marine ecosystem models from two Australian organizations. We found that costs varied by two orders of magnitude, and that ecosystem model costs increased with model complexity. Using these costs, we walk through a hypothetical example of cost‐benefit analysis. The demonstration is intended to catalyze the reporting of modeling costs and benefits.

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, tangelo oil, expressed, CAS Registry Number 72869-73-9, RIFM ID 931-G2.5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-(p-isopropylphenyl)propionaldehyde, CAS registry number 7775-00-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,3,5-trimethylcyclohexyl ethyl ether, CAS Registry Number 67583-77-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, triethyltrimethyl-2-cyclohexen-1-one, CAS Registry Number 68845-35-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl vanillate, CAS Registry Number 3943-74-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, germacrene D, CAS Registry Number 23986-74-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-methyl-2-thiophenecarboxaldehyde, CAS registry number 13679-70-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isoeugenyl benzyl ether, CAS Registry Number 120-11-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, pentyl benzoate, CAS Registry Number 2049-96-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl vanillin isobutyrate, CAS Registry Number 188417-26-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, l-carvone, CAS Registry Number 6485-40-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, butyl benzoate, CAS Registry Number 136-60-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, p-isopropyl phenylacetaldehyde, CAS Registry Number 4395-92-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl benzoate, CAS Registry Number 93-58-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexane, 1-(1,1-dimethylpropyl)-4-ethoxy-, cis-, CAS Registry Number 181258-87-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-methyl-3-decen-5-ol, CAS Registry Number 81782-77-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isoeugenol, CAS registry number 97-54-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 10-undecen-1-yl acetate, CAS Registry Number 112-19-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-2-pentenoic acid, CAS Registry Number 16957-70-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 6,10-dodecadienal, 3,7,11-trimethyl-, (3S,6E)-, CAS registry number 194934-66-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, cuminyl nitrile, CAS registry number 13816-33-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, (Z,Z)-1,1'-[ethylidenebis(oxy)]di(hex-3-ene), CAS Registry number 63449-64-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl benzoate, CAS Registry Number 93-89-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-methyl-5-phenyl-3-hexanone, CAS Registry Number 4927-36-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, (E)-1-(1-methoxypropoxy)hex-3-ene, CAS Registry Number 97358-54-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl undec-10-enoate, CAS registry number 111-81-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, acetaldehyde ethyl cis-3-hexenyl acetal, CAS Registry Number 28069-74-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, α-amylcinnamaldehyde, CAS Registry Number 122-40-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 9-decenyl acetate, CAS Registry Number 50816-18-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, terpinyl acetate (isomer mixture), CAS Registry Number 8007-35-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, butyric acid, CAS Registry Number 107-92-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phenol, 4-(3,6-dihydro-4-methyl-2H-pyran-2-yl)-2-methoxy-, CAS Registry Number 128489-02-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, eucalyptol, CAS Registry Number 470-82-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, terpineol, CAS Registry Number 8000-41-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 7-methyl-2H-benzo-1,5-dioxepin-3(4H)-one, CAS Registry Number 28940-11-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, santalol, CAS Registry Number 11031-45-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-sec-butylcyclohexanone, CAS Registry Number 14765-30-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, citronellyl crotonate, CAS Registry Number 68039-38-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, o-methoxybenzaldehyde, CAS Registry Number 135-02-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-(isopropyl)cyclohexyl propionate, CAS Registry Number 63449-95-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, dextro-verbenone, CAS Registry Number 18309-32-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, pyridine, 5-hexyl-2-methyl-, CAS Registry Number 710-40-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-methyl-2,4-nonedione, CAS Registry Number 113486-29-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, dodecahydro-3,8,8,11a-tetramethyl-5H-3,5a-epoxynaphth[2,1-c]oxepin, CAS Registry Number 57345-19-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-pentylcyclopentan-1-one, CAS Registry Number 4819-67-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, butyl 2-methylcrotonate (Z), CAS registry number 7785-64-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-2-butyl acetate, CAS Registry Number 103-07-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phenethyl cinnamate, CAS Registry Number 103-53-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, hexyl tiglate, CAS Registry Number 16930-96-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-3-buten-2-ol, CAS Registry Number 115-18-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,6,10-trimethylundeca-5,9-dienol, CAS Registry Number 24048-14-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl valerate, CAS Registry Number 539-82-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl sorbate, CAS Registry Number 689-89-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-phenylpropyl cinnamate, CAS Registry Number 122-68-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isoamyl isovalerate, CAS registry number 659-70-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methylpropyl 2-methylbutyrate, CAS Registry Number 2445-67-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-6-octenoic acid, CAS Registry Number 502-47-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, diethyl 1,4-cyclohexane dicarboxylate, CAS Registry Number 72903-27-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl valerate, CAS Registry Number 624-24-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-methyl-4-phenyl-2-pentanone, CAS Registry Number 7403-42-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 2,4,7-decatrienoate, CAS Registry Number 78417-28-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2(3H)-benzofuranone, hexahydro-3,6-dimethyl-, CAS Registry Number 92015-65-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isobutyl angelate, CAS Registry Number 7779-81-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methylpyrazine, CAS Registry Number 109-08-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 5-ethylidenebicyclo[2.2.1]hept-2-yl propionate, CAS Registry Number 73347-77-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-heptyltetrahydrofuran, CAS Registry Number 2435-16-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, o-toluenethiol, CAS Registry Number 137-06-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzoic acid, 2-hydroxy-5-methyl-, methyl ester, CAS Registry Number 22717-57-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-hexanone, 5-mercapto-5-methyl-, CAS Registry Number 851768-51-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-acetoxy-3-ethoxybenzaldehyde, CAS Registry Number 72207-94-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, anisyl acetate (isomer unspecified), CAS Registry Number 1331-83-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-methylquinoxaline, CAS Registry Number 13708-12-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, terpinyl formate, CAS Registry Number 2153-26-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-ethyl-5-methylpyrazine, CAS registry number 13360-64-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-isobutyl-3-methoxypyrazine, CAS registry number 24683-00-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,5-heptadien-1-ol, 1-acetate, (3Z,5E)-, CAS Registry Number 86611-09-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-ethyl-3-methylpyrazine, CAS Registry Number 15707-23-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,5-dimethylbicyclo[3.2.1]octan-8-one-oxime, CAS Registry Number 75147-23-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, acetic acid, CAS Registry Number 64-19-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isopropoxy ethyl salicylate, CAS Registry Number 79915-74-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 2-methoxybenzoate, CAS Registry Number 7335-26-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-pentenoic acid, 2-methyl-, hexyl ester, CAS Registry Number 85508-08-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, α-methylcinnamaldehyde, CAS Registry Number 101-39-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl 2-pyrrolyl ketone, CAS Registry Number 1072-83-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-methyl-2-buten-1-ol, CAS registry number 556-82-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, β-phellandrene, CAS Registry Number 555-10-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,3-diethyl-5-methylpyrazine, CAS Registry Number 18138-04-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1-oxaspiro[4.5]deca-3,6-diene, 2,6,9,10-tetramethyl-, CAS Registry Number 71078-31-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,4,5-trimethylthiazole, CAS Registry Number 13623-11-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, propionic acid, CAS Registry Number 79-09-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, α-methylbenzyl isobutyrate, CAS Registry Number 7775-39-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, geranyl propionate, CAS Registry Number 105-90-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 11-oxahexadecanolide, CAS Registry Number 3391-83-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, acetyl cedrene, CAS Registry Number 32388-55-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-3,5 or 6-ethoxypyrazine, CAS Registry Number 32737-14-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-benzodioxole, 5-(diethoxymethyl)-, CAS Registry Number 40527-42-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl phenylacetate, CAS Registry Number 101-41-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl o-methoxybenzoate, CAS registry number 606-45-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, citral propylene glycol acetal, CAS Registry number 10444-50-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutanol, CAS Registry Number 137-32-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, (E)-2-phenylpropenyl acetate, CAS registry number 37973-51-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, hexyl methacrylate, CAS Registry Number 142-09-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl benzoylacetate, CAS registry number 94-02-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ocimenyl acetate, CAS Registry Number 72214-23-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, pyridine, 4-[1(4-,5 or 6)-methylbicyclo[2.2.1]hept-5-en-2-yl]-, CAS Registry Number 862079-91-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl trans-2-octenoate, CAS Registry Number 2396-85-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3,5-undecatriene, CAS Registry Number 16356-11-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl formate, CAS Registry Number 109-94-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexahydro-3H-benzofuran-2-one, CAS Registry Number 6051-03-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, nerolidol (isomer unspecified), CAS Registry Number 7212-44-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, paraldehyde, CAS Registry Number 123-63-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, pyrazine, 2-methoxy-3-(4-methylpentyl)-, CAS Registry Number 68844-95-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-acetylmercaptohexyl acetate, CAS Registry Number 136954-25-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, (3-methoxy-2-methylpropyl)benzene, CAS Registry Number 120811-92-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-heptylcyclopentanone, CAS Registry Number 137-03-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,4,4,7-tetramethylnona-6,8-diene-3-one-oxime, CAS Registry Number 81783-01-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, citronellyl 3-methyl-2-butenoate, CAS Registry Number 20770-40-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, acetaldehyde ethyl linalyl acetal, CAS Registry Number 40910-49-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-3-furanthiol, CAS Registry Number 28588-74-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, pentyl phenylacetate, CAS Registry Number 5137-52-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, furfuryl methyl sulfide, CAS Registry Number 1438-91-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cinnamyl nitrile, CAS Registry Number 1885-38-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl trimethylhexanoate, CAS Registry Number 68132-80-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, carvacrol, CAS Registry Number 499-75-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 5- and 6-decenoic acid, CAS Registry Number 72881-27-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, hexyl octanoate, CAS Registry Number 1117-55-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2H-inden-2-one, 1,3-dihydro-, CAS Registry Number 615-13-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, hydroxycitronellol, CAS Registry Number 107-74-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, geranyl isovalerate, CAS Registry Number 109-20-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, formic acid, CAS Registry number 64-18-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-octen-3-ol, CAS Registry Number 3391-86-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phenylacetaldehyde 2,4-dihydroxy-2-methylpentane acetal, CAS Registry Number 67633-94-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalool oxide, CAS Registry Number 1365-19-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, geranyl isobutyrate, CAS Registry Number 2345-26-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-dimethyl-3-phenylbutyl acetate, CAS Registry Number 68083-58-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phytol, CAS Registry Number 150-86-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, anisyl formate, CAS registry number 122-91-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexanone,5-methyl-2-(1-methylethyl)-,oxime, CAS registry number 19096-86-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, patchouli alcohol, CAS Registry Number 5986-55-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, propyl butyrate, CAS Registry Number 105-66-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-ethyl-2,6-dimethylpyrazine, CAS Registry Number 13925-07-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5,6,7-trimethylocta-2,5-dien-4-one, CAS Registry Number 358331-95-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, (1R,2S,5R)-N-(4-methoxyphenyl)-5-methyl-2-(1-methylethyl)cyclohexanecarboxamide, CAS Registry Number 68489-09-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzoic acid, 2-[(2-phenylethylidene)amino]-, methyl ester, CAS Registry Number 67785-76-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, butyl salicylate, CAS Registry Number 2052-14-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cycloionone, CAS Registry Number 5552-30-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, geranyl butyrate, CAS Registry Number 106-29-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, geranyl formate, CAS Registry Number 105-86-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methylpropyl 3-methylbutyrate, CAS Registry Number 589-59-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl phenylacetate, CAS Registry Number 101-97-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, butyl butyryllactate, CAS Registry Number 7492-70-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ω-6-hexadecenlactone, CAS Registry Number 7779-50-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-isobutyl-3-methylpyrazine, CAS Registry Number 13925-06-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-tert-butylcyclohexanol, CAS Registry Number 98-52-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,5-dimethylpyrazine, CAS Registry Number 123-32-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, α,α-dimethylphenylethyl propionate, CAS Registry Number 67785-77-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, eugenyl methyl ether, CAS Registry Number 93-15-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, β-ionol, CAS Registry Number 22029-76-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, hexyl salicylate, CAS Registry Number 6259-76-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ocimenol, CAS Registry Number 5986-38-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,4-dihydro-5-methylnaphthalen-1(2H)-one, CAS Registry Number 6939-35-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, decahydro-β-naphthyl formate, CAS Registry Number 10519-12-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-hydroxy-3-pentenoic acid lactone, CAS Registry number 591-12-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-ethyl-3-hydroxy-4-methyl-2(5H)-furanone, CAS Registry Number 698-10-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Effects of climate change on marine coastal ecosystems – A review to guide research and management - Ewan Trégarot; Juan Pablo D'Olivo; Andrea Zita Botelho; Andrea Cabrito; Gabriel O. Cardoso; Gema Casal; Cindy C. Cornet; Simon M. Cragg; A. Karima Degia; Stein Fredriksen; Elisa Furlan; Georg Heiss; et al. (Biological Conservation, 2024)

Evaluating the efficiency of different sampling techniques to survey non-flying small mammals in the Amazon - André L. M. Botelho; Paulo S. D’Andrea; Charle F. Crisóstomo; Marcos Silveira; Camila S. Lucio; Pedro Z. L. Santos; Cibele R. Bonvicino; Rosana Gentile (Mammal Research, 2024)
Small non-flying mammals represent 44% of Brazilian mammal species and have a wide range of habits and life-history strategies. This wide diversity requires different sampling methods in survey studies. We compared the efficiency of pitfall and live-traps in different vertical positions in relation to the alpha and beta diversity of small mammals in three forest fragments with different levels of conservation and in a continuous area in the southwestern Amazon, Acre state. Captures were carried out using a combination of pitfall traps and live-traps on the ground, understorey, and canopy. Taxonomic identification was performed by morphological and molecular analyses. Alpha diversity was evaluated using Hill numbers ( q = 0 and q = 1). The turnover between different types of traps and different vertical strata (beta diversity) was analysed using permutation analysis of variance. Species richness between areas ranged from 6 to 21. The highest species richness was observed in ground traps, and the lowest species richness was observed in the canopy. Live-traps on the ground recorded a greater diversity in two areas. Pitfall traps recorded the greatest number of unique species in three areas. The different types of traps and the different vertical positions acted in a complementary way in the small mammal samplings. The turnover in relation to trap type and stratum indicated the formation of two significantly different groups: ground traps and aboveground traps. However, the use of canopy traps did not contribute significantly to an increase in the estimated species richness and diversity in three of the four localities.

Electronic waste in emerging countries: current scenario of generation, policies, and recycling technologies regarding the coronavirus pandemic - A. B. Botelho Junior; M. D. C. R. da Silva; P. S. S. Camargo; D. D. Munchen; M. P. Cenci; D. A. Bertuol; H. M. Veit; J. A. S. Tenório; D. C. R. Espinosa (International Journal of Environmental Science and Technology, 2024)

RIFM fragrance ingredient safety assessment, allyl cyclohexaneacetate, CAS Registry Number 4728-82-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 1,3,4,6,7,8-hexahydro-4,6,6,7,8,8-hexamethylcyclopenta-γ-2-benzopyran, CAS Registry Number 1222-05-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, benzene, 1-(dimethoxymethyl)-4-methoxy-, CAS Registry Number 2186-92-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, α-isobutylphenethyl alcohol, CAS Registry Number 7779-78-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, anisyl propionate, CAS Registry Number 7549-33-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, octahydrocoumarin, CAS Registry Number 4430-31-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, ethyl 2-methyl-3,4-pentadienoate, CAS Registry Number 60523-21-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 3,4-dimethylthiophene, CAS Registry Number 632-15-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, tetrahydro-4-methyl-2-(2-methylpropen-1-yl)pyran, CAS Registry Number 16409-43-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, camphene, CAS Registry Number 79-92-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, linalool oxide pyranoid, CAS Registry Number 14049-11-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 3a,4,4a,5,8,8a,9,9a-octahydro-4,9:5,8-dimethano-1H-benz[f]indene, CAS Registry Number 7158-25-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, salicylaldehyde, CAS Registry Number 90-02-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2-(1-(3′,3′-dimethyl-1′-cyclohexyl)ethoxy)-2-methyl propyl propanoate, CAS Registry Number 141773-73-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2-methoxy-3-methylpyrazine, CAS Registry Number 2847-30-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, propyl (2S)-2-(1,1-dimethylpropoxy)-propanoate, CAS Registry Number 319002-92-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, cyclohexaneethanethiol, 3-mercapto-b,4-dimethyl-, CAS Registry Number 4802-20-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, decahydro-β-naphthyl acetate, CAS Registry Number 10519-11-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, N-p-benzeneacetonitrilementhanecarboxamide, CAS Registry Number 852379-28-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, benzyl propionate, CAS Registry Number 122-63-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, dimethyl succinate, CAS Registry Number 106-65-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 3-mercaptohexyl acetate, CAS Registry Number 136954-20-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 1-methylnaphthalene, CAS Registry Number 90-12-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 5-hydroxy-2,4-decadienoic acid δ-lactone, CAS Registry Number 27593-23-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, allyl (3-methylbutoxy)acetate, CAS Registry Number 67634-00-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, amyl isobutyrate, CAS Registry Number 2445-72-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 1,7,7-trimethylbicyclo[4.4.0]dec-3-yl acetate, CAS Registry number 24238-95-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, trans-2-hexenoic acid, CAS Registry Number 13419-69-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, acetaldehyde ethyl phenylethyl acetal, CAS Registry Number 2556-10-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, farnesol, CAS Registry Number 4602-84-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 4,7,7-trimethyl-2-(3-methyl-2-butenyl)bicyclo[4.1.0]heptan-3-one, CAS Registry Number 74499-58-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2,4,6-cycloheptatrien-1-one, 2-hydroxy-4-(1-methylethyl)-, CAS Registry Number 499-44-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, ethylene dodecanedioate, CAS Registry Number 54982-83-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, 2,2,5-trimethyl-5-pentylcyclopentanone, CAS Registry Number 65443-14-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, benzoic acid, 2-hydroxy-, 2-methylbutyl ester, CAS Registry Number 51115-63-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, α,α-dimethylphenethyl butyrate, CAS Registry Number 10094-34-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, isoamyl hexanoate, CAS registry number 2198-61-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, ethyl 3-phenylpropionate, CAS Registry Number 2021-28-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2-ethyl-4-(2,2,3-trimethyl-3-cyclopenten-1-yl)-2-buten-1-ol, CAS Registry number 28219-61-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 1,1-dimethyl-2-phenylethyl acetate, CAS registry number 151-05-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 1,5,7-octatrien-3-ol, 3,7-dimethyl-, (5E)-, CAS Registry Number 53834-70-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2-pyridinecarboxylic acid, ethyl ester, CAS Registry Number 2524-52-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, tetrahydro-4-methyl-2-phenyl-2H-pyran, CAS Registry Number 94201-73-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, linalyl benzoate, CAS Registry Number 126-64-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, butyl phenylacetate, CAS Registry Number 122-43-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, 3-ethylhexahydro-2(3H)-benzofuranone, CAS Registry Number 54491-17-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, isodecyl alcohol, CAS Registry Number 25339-17-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 4,5-dimethyl-3-hydroxy-2,5-dihydrofuran-2-one, CAS Registry Number 28664-35-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 1-(4-hydroxy-3-methoxyphenyl)decan-3-one, CAS registry number 27113-22-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 5H-5-methyl-6,7-dihydrocyclopenta(b)pyrazine, CAS Registry Number 23747-48-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, (±) ethyl 3-mercaptobutyrate, CAS Registry Number 156472-94-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, l-lactic acid (2-hydroxy propionic acid), CAS Registry Number 79-33-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, dihydronootkatone, CAS Registry Number 20489-53-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 9-hexadecyn-8-one, CAS Registry Number 89319-68-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, yuzunone, CAS Registry Number 1009814-14-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 4-methoxybenzaldehyde diethyl acetal, CAS Registry Number 2403-58-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, dl-citronellol, CAS Registry Number 106-22-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, estragole, CAS registry number 140-67-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 3-hexenyl 2-oxopropionate, CAS Registry Number 68133-76-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, methoxypyrazine, CAS registry number 3149-28-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, myrcenol, CAS Registry Number 543-39-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, diethyl succinate, CAS Registry Number 123-25-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, menthone, CAS Registry Number 10458-14-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2-methyl-4-(2,6,6-trimethylcyclohex-1-en-1-yl)-2-butenal, CAS registry number 3155-71-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, isobutyl salicylate, CAS Registry Number 87-19-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, propyl phenethyl acetal, CAS registry number 7493-57-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, sssmenthadiene-7-methyl formate, CAS registry number 68683-20-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; MsA. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 5,6,7,8-tetrahydroquinoxaline, CAS registry number 34413-35-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, (Z)-5-(3-hexenyl)dihydrofuran-2(3H)-one, CAS Registry Number 63095-33-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2-methyldecanal, CAS Registry Number 19009-56-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, nerol, CAS Registry Number 106-25-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2-acetyl-3-methylpyrazine, CAS Registry number 23787-80-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

One-year variation in quantity and properties of microplastics in mussels (Mytilus galloprovincialis) and cockles (Cerastoderma edule) from Aveiro lagoon - M.J. Botelho; C. Vale; F. Marques; C. Moreirinha; S.T. Costa; L. Guilhermino; S. Joaquim; D. Matias; M. Candeias; A. Rudnitskaya (Environmental Pollution, 2023)

RIFM fragrance ingredient safety assessment, 2,4-hexadienyl isobutyrate, CAS Registry number 16491-24-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2-phenylhexanenitrile, CAS registry number 3508-98-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, diphenylmethane, CAS Registry Number 101-81-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2-methyl-3-(1-oxopropoxy)-4H-pyran-4-one, CAS Registry Number 68555-63-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, ethyl p-anisate, CAS registry number 94-30-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 4-hydroxybenzaldehyde, CAS registry number 123-08-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 6,6-dimethoxy-2,5,5-trimethylhex-2-ene, CAS registry number 67674-46-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, isoamyl octanoate, CAS registry number 2035-99-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2,3,3-trimethylindanone, CAS registry number 54440-17-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2,3-dethylpyrazine, CAS registry number 15707-24-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2-methoxy-3(5 and 6)-isopropylpyrazine, CAS Registry Number 25773-40-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2-acetylthiophene, CAS registry number 88-15-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, petitgrain mandarin oil, CAS registry number 8014-17-3, RIFM ID: 250-E2.12 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2-octenoic acid, 4-ethyl-, (2E)-, CAS Registry Number 60308-76-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2,11-dodecadienal, (E)- (9CI), CAS registry number 118635-60-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, citronellyl tiglate, CAS Registry Number 24717-85-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, guaiacyl phenylacetate, CAS Registry Number 4112-89-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2,6-dimethylpyrazine, CAS registry number 108-50-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2,6-dimethyl-10-methylene-2,6,11-dodecatrienal, CAS registry number 17909-77-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2,3,5-trimethylpyrazine, CAS registry number 14667-55-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, (+-)-ethyl 3-mercapto-2-methylbutanoate, CAS Registry Number 888021-82-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, 3-methylbutyl 2-methylpropanoate, CAS Registry Number 2050-01-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment,2-methyl-2-propanol, CAS registry number 75-65-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; M. Date; W. Dekant; C. Deodhar; A.D. Fryer; et al. (Food and Chemical Toxicology, 2023)

Correction: Phylogeny of Didelphid marsupials (Didelphimorphia) from Acre, western Amazonia - Cibele R. Bonvicino; Ana Lazar; Cintia Povill; Fabiana P. Caramaschi; Tatiana P. T. de Freitas; Charle F. Crisóstomo; André L. M. Botelho; Paulo S. D’Andrea (Mammalian Biology, 2022)

Phylogeny of Didelphid marsupials (Didelphimorphia) from Acre, western Amazonia - Cibele R. Bonvicino; Ana Lazar; Cintia Povill; Fabiana P. Caramaschi; Tatiana P. T. de Freitas; Charle F. Crisóstomo; André L. M. Botelho; Paulo S. D’Andrea (Mammalian Biology, 2022)

Are the current commercially available oximes capable of reactivating acetylcholinesterase inhibited by the nerve agents of the A-series? - Marcelo C. Santos; Fernanda D. Botelho; Arlan S. Gonçalves; Daniel A. S. Kitagawa; Caio V. N. Borges; Taynara Carvalho-Silva; Leandro B. Bernardo; Cíntia N. Ferreira; Rafael B. Rodrigues; Denise C. Ferreira Neto; Eugenie Nepovimova; Kamil Kuča; et al. (Archives of Toxicology, 2022)

Characteristics and mechanisms of multistage dolomitization in Proterozoic dolomitic breccia from Água Clara Formation, Ribeira Belt, Brazil - Murilo Henrique Taques Camargo; André D. Ferreira; Cristina V. Pinto-Coelho; Lucilia A. R. de Oliveira; Marcella L. Cavallari; Lorena de F. Alfaro; Alberto C. Botelho; Júlio T. Brita; Cláudio N. Lamarão; Gisele T. Marques; Eduardo Roemers-Oliveira (Carbonates and Evaporites, 2022)

In Vivo Cardiotoxic Potential of Micrurus frontalis Venom - Marthin R. Lempek; Ana F. M. Botelho; Paula B. U. Fernandes; Vitor M. Ribeiro; Carlos C. D. Olórtegui; Marília M. Melo (Cardiovascular Toxicology, 2022)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Synthesis of piplartine analogs and preliminary findings on structure–antimicrobial activity relationship - Antonio Maciel Fregnan; Guilherme Andrade Brancaglion; Alexandre Francisco Cerqueira Galvão; Cinara Oliveira D’Sousa Costa; Diogo Rodrigo Magalhães Moreira; Milena Botelho Pereira Soares; Daniel Pereira Bezerra; Naiara Chaves Silva; Stella Maria de Souza Morais; Josidel Conceição Oliver; Amanda Latercia Tranches Dias; Luiz Felipe Leomil Coelho; et al. (Medicinal Chemistry Research, 2017)

Effects of maternal diabetes on male offspring: high cell proliferation and increased activity of MMP-2 in the ventral prostate - A. A. Damasceno; C. P. Carvalho; E. M. B. Santos; F. V. Botelho; F. A. Araújo; S. R. Deconte; T. C. Tomiosso; A. P. C. Balbi; R. G. Zanon; S. R. Taboga; R. M Góes; D. L. Ribeiro (Cell and Tissue Research, 2014)

Infective endocarditis in intravenous drug abusers: an update - C. Sousa; C. Botelho; D. Rodrigues; J. Azeredo; R. Oliveira (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Host, pathogen and treatment-related prognostic factors in rickettsioses - E. Botelho-Nevers; D. Raoult (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Coxiella burnetii infection of aortic aneurysms or vascular grafts: report of 30 new cases and evaluation of outcome - E. Botelho-Nevers; P.-E. Fournier; H. Richet; F. Fenollar; H. Lepidi; C. Foucault; A. Branchereau; P. Piquet; M. Maurin; D. Raoult (European Journal of Clinical Microbiology & Infectious Diseases, 2007)